ANALISA KERJA SAMA PT. MEDIATAMA BINAKREASI DENGAN MEDIA PARTNER DALAM PENYELENGGARAAN PAMERAN INACRAFT 2018 DI JAKARTA CONVENTION CENTER - Gilang Ramadhan; Lenny Yusrini (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
This research aims to analyze the partnership between PT. Mediatama Binakreasi and the media partners in the Inacraft Exhibition 2018. The method used is the SWOT analysis by identifying the potential components of the agreement stated at the Letter of Agreement (LoA) between PT. Mediatama Binakreasi and the media partners. The result of this research shows that the SWOT components identified are all in the first quadrant, or in other words, the agreement has a strong internal position and can be developed further using agrressive strategy.